2016
DOI: 10.1002/gps.4408
|View full text |Cite
|
Sign up to set email alerts
|

A change in social activity affect cognitive function in middle‐aged and older Koreans: analysis of a Korean longitudinal study on aging (2006–2012)

Abstract: Promotion of participation in religious organizations, friendship organizations, and family/school reunions (only for older persons) may help preserve cognitive function in individuals aged 45 years or older in Korea. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 33 publications
(41 reference statements)
6
51
0
Order By: Relevance
“…These results suggested that continued participation in social activities was associated with decreased risk of cognitive function decline. This is consistent with ndings on the associations between social participation and cognitive function (44,45). A previous longitudinal study of community-dwelling adults and older adults suggested that maintaining many social activities may help prevent and delay cognitive function (44).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results suggested that continued participation in social activities was associated with decreased risk of cognitive function decline. This is consistent with ndings on the associations between social participation and cognitive function (44,45). A previous longitudinal study of community-dwelling adults and older adults suggested that maintaining many social activities may help prevent and delay cognitive function (44).…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with ndings on the associations between social participation and cognitive function (44,45). A previous longitudinal study of community-dwelling adults and older adults suggested that maintaining many social activities may help prevent and delay cognitive function (44). A Taiwanese cohort study also showed that participating in more social activities reduces the risk of cognitive impairment (46).…”
Section: Discussionsupporting
confidence: 88%
“…Substantial research has explored the risks and protective factors of cognitive impairment. Based on previous studies, the following are all closely associated with cognitive impairment: sociodemographic variables such as age, education, and marital status 3,4 ; physical conditions and diseases such as high blood pressure, diabetes, and cardiovascular disorders [4][5][6] ; health-related behaviours such as smoking, alcohol consumption, and regular exercise 7,8 ; physical function 9,10 ; and social participation involving, for example, social gatherings, religious activities, and volunteer work. 11,12 As individuals age, the risk of physiological diseases increases, and such diseases and conditions that are common among the elderly, such as high blood pressure, diabetes, and stroke, may be associated with cognitive decline.…”
Section: Introductionmentioning
confidence: 99%
“…An aged society, where the percentage of the aged population is 14% of the total population, will start in 2018; and a super aged society, where the percentage of aging people is 20% of entire population, will begin in 2026 . The population aged >65 years will increase to 12.7 million (24.3% of the entire population) in 2030, and they will account for 37% of the total population in 2050 . This rapid growth of the elderly population leads to increased medical costs .…”
Section: Introductionmentioning
confidence: 99%
“…1 The population aged >65 years will increase to 12.7 million (24.3% of the entire population) in 2030, and they will account for 37% of the total population in 2050. 2 This rapid growth of the elderly population leads to increased medical costs. 3 Elderly health insurance expenditure per capita was KRW3.3 million in 2015, and the expense size is 2.9-fold compared with the total health insurance expenditure per capita, which is KRW1.2 million.…”
Section: Introductionmentioning
confidence: 99%